A Case of Polymicrobial, Gram-Negative Pulmonic Valve Endocarditis. (28th March 2019) - Bekker, Tatiana; Govind, Anusha; Weber, Devin M.
Abstract : Infective endocarditis due to Gram-negative, non-HACEK bacteria is a rare clinical entity. Even moreso, isolated pulmonic valve endocarditis accounts for less than 1.5–2% of all cases of infective endocarditis. These disease pathologies commonly occur in the setting of intravenous drug abuse, indwelling catheters or cardiac devices, or underlying structural heart disease. We present a unique case of pulmonic valve endocarditis in the setting of persistent polymicrobial bacteremia with Klebsiella pneumoniae and Citrobacter koseri with recent gastrointestinal instrumentation evolving into isolated pulmonic valve endocarditis.